Analyzing Kim Jong‐un's Survival Strategy from the Comparative Authoritarian Perspective*. (8th August 2016) - Koo, Bon Sang; Choi, Jun Young; Kim, Junseok
Abstract : This paper shows that we can properly analyze Kim Jong‐un's survival strategy by employing the knowledge accumulated in comparative studies of contemporary authoritarianism . According to Geddes et al .'s classification, North Korea belongs to a hybrid type that possesses the characteristics of the personalist and single‐party types. Recent comparative studies demonstrate that personalist rulers who are not convinced of their firm control of the military tend to hesitate to strengthen it, even though they know that the military is the most effective tool for controlling threats by political elites and the general public. This theoretically explains why the young ruler who experienced a short power succession period did not continue his father's "military‐first policy, " and his divide‐and‐rule approach is inevitably different from his father's. Accordingly, we expect that the ruler of the unconsolidated regime will target the core of the military, the army faction, and utilize security forces as typical personalist rulers do. These are supported in practice. We also observe that Kim Jong‐un controls the military by utilizing the organizations of the institutionalized party, the Korean Workers' Party, and appointing party officers to key posts in the military. This positively affects his regime stability, which distinguishes his regime from the pure personalist type.